2021
DOI: 10.2807/1560-7917.es.2021.26.4.1900762
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and severity of pertussis hospitalisations in infants aged less than 1 year in 37 hospitals of six EU/EEA countries, results of PERTINENT sentinel pilot surveillance system, December 2015 to December 2018

Abstract: Introduction PERTINENT is a pilot active surveillance system of infants hospitalised with pertussis in six European Union/European Economic Area countries (37 hospitals, seven sites). Aim This observational study aimed to estimate annual pertussis incidence per site from 2016 to 2018 and respective trends between 2017 and 2018. Pertussis cases were described, including their severity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Parents were more frequently tested as positive contact (66.0%), followed by siblings (24.5%). This relationship with infant and age distribution of primary case contacts was recently shown to be similar in HIC where aPVs are used [ 24 ]. The important rate of pertussis infection among contact cases observed herein highlights the underreporting among older children and adults and are in line with studies evidencing substantial circulation of pertussis among Iranian children and adolescents [ 10 , 25 ].…”
Section: Discussionmentioning
confidence: 66%
“…Parents were more frequently tested as positive contact (66.0%), followed by siblings (24.5%). This relationship with infant and age distribution of primary case contacts was recently shown to be similar in HIC where aPVs are used [ 24 ]. The important rate of pertussis infection among contact cases observed herein highlights the underreporting among older children and adults and are in line with studies evidencing substantial circulation of pertussis among Iranian children and adolescents [ 10 , 25 ].…”
Section: Discussionmentioning
confidence: 66%
“…According to the PERTINENT surveillance system, a significant decrease in pertussis incidence rates was observed in France in infants between 2017 (49.1; 95% CI: 39.5-60.3) and 2018 (34.7; 95% CI: 26.7-44.4), corresponding to an incidence rate ratio of 0.71 (p = 0.034) [7]. Between these 2 years, incidence rate ratios were 1.43 in Czechia (p = 0.468), 0.25 in Catalonia, Spain (p = 0.002), 0.21 in Navarra, Spain (p = 0.148), 0.14 in Ireland (p = 0.002), 0.63 in Italy (p = 0.053), and zero in Norway [7]. Our estimates of incidence for infants in 2017 (84; 95% CI: 0-204) were comparable to those of PERTINENT estimates, while they were well below for 2018 (0; 95% CI: 0-0).…”
Section: Discussionmentioning
confidence: 99%
“…Microbiologists are encouraged to send the isolates to the National Reference Center for Whooping Cough, and typically do so [6]. In 2015, the European Centre for Disease Prevention and Control (ECDC) set up 'Pertussis in Infants European Network' (PERTINENT), a hospitalbased active pilot surveillance system that involves 41 hospitals from six countries, including 21 French hospitals participating in the Renacoq surveillance [7]. This system monitors laboratory-confirmed cases of pertussis (by PCR and/or culture) among infants attending hospitals participating in the network [7].…”
Section: Introductionmentioning
confidence: 99%
“…It might be the same for FHA(−) strains. During the Pertinent study, a European hospital-based study, some patients were biologically confirmed by PCR but did not have symptoms, suggesting that they might have been infected by a PT(−) strain [ 46 ]. It will then be of interest to follow the clinical symptoms of patients with a positive pertussis PCR, including coinfections, according to their age, vaccination status and contacts.…”
Section: Pertussismentioning
confidence: 99%